Education In Poverty Reduction: A Systematic Literature Review - Panduwinata, Lifa Farida; Subroto, Waspodo Tjipto; Sakti, Norida Candra (PT. Maju Malaqbi Makkarana, 2025)
Human resource development through education is frequently linked to the worldwide problem of poverty reduction. Education is essential in building human resources to improve skills and knowledge to get good job opportunities. This article analyses the existing literature on how education can reduce poverty. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement was used as the review methodology, and a systematic review of the Google Scholar database was carried out using Publish or Perish, which identified 99 relevant studies. In this review, education is usually evaluated from two aspects: the quality and the education level. The results of this review confirm the general conclusion that education is an essential tool for poverty reduction. Through education, people acquire knowledge and skills that can be used to get better jobs and ultimately reduce poverty. Some of the recommendations are more development research to improve the quality of education, and education policies must focus on long-term investments to overcome poverty.